Analysis of Time and Frequency of Implementation of Non-Communicable Disease Integrated Guidance Posts in the New Normal Era in Binjai City - Hartatik, Hartatik; Aulia, Destanul; Lubis, Rahayu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study was to determine and analyze of time and frequency of implementation of non-communicable disease integrated guidance posts in the new normal era in Binjai City. This type of research is an analytic survey with a cross sectional design. The total population in this study was 179,650 with a total sample of 174 respondents obtained by purposive sampling. This research instrument uses a questionnaire that is used in the form of a google form. The data obtained in this study were analyzed by conjoint analysis. Based on the results of research on the people of Binjai City, the attribute activities of the non-communicable disease integrated guidance posts in the new normal era in Binjai City, the most important thing is the time of the implementation of the non-communicable disease integrated guidance posts, then the attribute activities of the non-communicable disease integrated guidance posts which are not too important are the frequency implementation of the non-communicable disease integrated guidance posts.